ANALISIS PENGENDALIAN INTERNAL PENGELUARAN KAS DANA BANTUAN OPERASIONAL PENYELENGGARAAN (BOP) DI RA AN-NAJM BEKASI UTARA - Idzuha Zuhru Viraf; Triana Yuniati; Cahyadi Husadha (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2023)
The Operational Assistance Fund (BOP) is provided by the government for each school unit entity that meets the criteria. This program is provided by the government to improve the quality of school education, reduce the cost of non-personnel operational activities, as well as help ease the burden on underprivileged people who want to send their children to school. BOP fund management can be channeled well if fund managers in the internal control system run as well as possible. Internal control must protect school coffers and cash expenditure documents so that the objectives of BOP funding can be achieved by school units. The purpose of this study is to test and analyze whether the internal control of BOP fund cash expenditure running in An-Najm RA Bekasi-Utara has been effective or not. This type of research is a case study with the object of research Proof of Cash Out in the period 2018 and 2019. Data in this study were obtained by means of documentation, interviews, observations. The data analysis technique used is stop or go sampling. The results of this internal control analysis research show the authorization of cash expenditures, lack of completeness of documents, and incompatibility of information with other documents. In the data collection technique through interviews, it can be concluded that the internal control running in the An-Najm Bekasi-Utara RA has not been in accordance with COSO. The 5 components imposed by COSO have not been fulfilled by RA An-Najm North Bekasi.